On the moisture migration of concrete subject to high temperature with different heating rates - Shen, Lei; Lo Monte, Francesco; Di Luzio, Giovanni; Cusatis, Gianluca; Li, Weixin; Felicetti, Roberto; Lombardi, Federico; Lualdi, Maurizio; Cao, Maosen; Ren, Qingwen (Cement and concrete research, 2021)
A better understanding of moisture migration in concrete at high temperature can play an important role to improve the fire-resistance and radiation-shielding capability of concrete structures. In this regard, within the numerical framework of Multi-physics Lattice Discrete Particle Model, the moisture clog in concrete during heating is defined as the moisture-saturated region between the so-called “water front” and “water back” (isosurfaces of saturation = 1). The moisture migration in concrete subject to slow and fast heating has been investigated by simulating experimental tests in which moisture has been monitored via different techniques, namely 3D Neutron Tomography and Ground-Penetrating Radar. An overall consistency between experimental and numerical results has been observed, indirectly proving the effectiveness of numerical modelling and experimental monitoring of moisture migration.